Possibility of the use of serological method for the determination of immunoglobuline a antibody against early antigene of Epstein-Barr virus as a marker in the diagnosis of nasopharyngeal tumors - Stošić-Divjak Svetlana; Đukić Vojko B.; Petrović Željko; Nešić Vladimir; Račić Alek J.; Tatić Zoran; Kanjuh Vladimir (Vojnosanitetski Pregled, 2005)
Background/Aim. According to the data from immunological, biological and molecular researches, there is a close association between the undifferentiated carcinoma of nasopharyngeal type (UCNT) and Epstein-Barr virus (EBV). To use IgA EA antibody as a serological marker in our patients with nasopharyngeal carcinoma from a clinical viewpoint. Methods. 91 patients were followed in the period from 1989−1998. In 11 of the patients the antibody titre serum for the early antigen of EBV virus were determinated before the treatment, and in 24 of the patients 3 years after the treatment. There were three control groups of patients: 20 voluntary blood donors, 26 patients with squamocellular laryngeal carcinoma, and 10 patients with squamocellular nasopharyngeal carcinoma. Results. In the group of 11 patients with UCNT before the treatment, the value of anti-EA IgA titre was 31.09, and in the patients after the treatment anti-EA IgA antiody titre was 14.56. In the control groups of patients the results were: in the blood donors 5.00; in the group with the diagnosis of squamocellular laryngeal carcinoma, the titre was 5.00; in the patients with squamocellular nosopharyngeal carcinoma, the titre anti-EA IgA was 5.36. Conclusion. These results were statistically highly significant (p < 0.01). Our research clearly showed that anti-EA IgA EBV marker could be useful in diagnosing, differential diagnosing and prognosing as well.